A variance-based information diffusion coefficient optimization algorithm and its application in missile effectiveness evaluation - Wang, Li; Tang, Xiaoan; Kong, Longxing; Jiang, Libing (2014 Communications Security Conference (CSC 2014), 2014)
In view of the problem that credibility of missile effectiveness evaluation model validation is not enough under the condition of incomplete samples, this paper introduces the information diffusion estimation theory, mainly studies the key issues-the optimization of diffusion coefficient in diffusion estimation, puts forward a variance-based algorithm to optimize information diffusion coefficient, theoretically derives the correctness of the algorithm, and proposes a method to evaluate the effectiveness of missile models on the strength of the algorithm. Experiments show that, the precision of information diffusion estimation adopting diffusion coefficient based on variance, is superior to the empirical equation algorithm. And the method evaluating the effectiveness of missile models could effectively implement the scientific verification and selection of the models.